2006
DOI: 10.1021/ie050941q
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Simulation of the Solid Suspension in a Stirred Slurry Reactor

Abstract: A comprehensive computational fluid dynamics CFD model was developed in the present study to gain insight into the solid suspension in a stirred slurry reactor. The preliminary simulations highlighted the need for the correct modeling of the interphase drag force. A two-dimensional model problem was then developed using CFD to understand the influence of free stream turbulence on the particle drag coefficient. The proposed correlation was then incorporated in a two-fluid model (Euler-Euler) along with the stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 29 publications
5
98
0
Order By: Relevance
“…Wadnerkar et al (2012) compared the effect of four drag models and found that the results from the modified Brucato drag model (Khopkar et al, 2006) were in reasonable agreement with the experimental data. Sardeshpande et al (2011) found that the coefficient in the Brucato drag model was dependent on the particle diameter, solids loading, particle Reynolds number, and prevailing turbulence.…”
Section: Reynolds Averaged Navier-stokes Simulationmentioning
confidence: 71%
See 3 more Smart Citations
“…Wadnerkar et al (2012) compared the effect of four drag models and found that the results from the modified Brucato drag model (Khopkar et al, 2006) were in reasonable agreement with the experimental data. Sardeshpande et al (2011) found that the coefficient in the Brucato drag model was dependent on the particle diameter, solids loading, particle Reynolds number, and prevailing turbulence.…”
Section: Reynolds Averaged Navier-stokes Simulationmentioning
confidence: 71%
“…Several drag force correlations (Clift et al, 1978;Magelli et al, 1990;Brucato et al, 1998;Pinelli et al, 2001;Khopkar et al, 2006) have been summarized (Ochieng and Onyango, 2010;Sardeshpande and Ranade, 2012). Wadnerkar et al (2012) compared the effect of four drag models and found that the results from the modified Brucato drag model (Khopkar et al, 2006) were in reasonable agreement with the experimental data.…”
Section: Reynolds Averaged Navier-stokes Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the outer region, the relatively small time derivative terms can be neglected. Upon comparing numerical predictions obtained from applying different impeller modeling methodologies, several investigators observed that steady state methods such as MRF can i. provide reasonable predictions to flow field features and power consumption (Jaworski et al, 2001;Bujalski et al, 2002;Kelly & Gigas, 2003;Khopkar et al, 2004;Aubin et al, 2004;Sommerfeld & Decker, 2004;Khopkar et al, 2006), and ii. save about one-seventh of the CPU-time (Brucato et al, 1998).…”
Section: Simulation Of Impeller Rotationmentioning
confidence: 99%